Introduction. Issue 1 (January 2016) - Cooley, Alexander
Abstract: The emergence of China, Korea and Japan as major external powers in Central Asia challenges our Eurocentric scholarly biases about the region's natural orientation and introduces new network ties, norms and organizations that will profoundly transform the region.